Exposure to lead and cadmium and associated factors in children 0–17 years of age living in an area contaminated by metals. Issue 3 (2nd April 2016) - Magna, Gustavo Alonso Muñoz; Machado, Sandro Lemos; Carvalho, Míriam de Fátima; de Almeida, Maria da Conceição Chagas; Vieira Moreno, Maria Lucia; Alva, Juan Carlos Rossi; Porsani, Milton José
ABSTRACT: This article analyzes some characteristics and conditions associated with Pb and Cd exposure using an exploratory approach, relating them to the levels of Pb and Cd in blood (blood lead levels [BLL] and blood cadmium levels [BCL]) in children 0–17 years of age living in an area contaminated by metals. BLL and BCL values were determined for each child and questionnaires were applied to their parents. Significant differences were found in mean BLL values according to race ( p = .03), family history of intoxication by Pb ( p = .004), if a family member was a metallurgy worker ( p = .047), if a family member performed activities in the area of metallurgy ( p = .03), and mother's employment status ( p = .014). The following characteristics were associated with increased risk of BLL above 5.0 mg/dL in children: race, having a family record of intoxication by lead, and having a parent who worked at the plant. BLC values are not significantly associated with any of the studied characteristics. It may be concluded that BLL values are influenced by the social indicators of the population.